Examen especial a la cartera de crédito en la cooperativa de ahorro y crédito indígena Sac ltda. ubicada en la ciudad de Ambato, en el período del 01 de enero al 31 de diciembre del 2014 - Clavijo Clavijo, Katherin Fernanda (2016)
This research was conducted at Indigena SAC saving and credit cooperative LTDA. This financial institution aims to provide support for the most vulnerable society that cannot access credit easily and quickly, helping economical development and social to improve the society´s life quality. The audit focused is vitally important to know it the financial data is true and reliable. A special examination audit includes the review and analysis of a particular account or transactions carried out after the execution, in order to verify the financial and administrative aspects in compliance with the laws and regulations then culminate with a final report which is given to know the observations….